Developing a Local Wisdom-Based “Patju” Religious Culture Model to Improve Students’ Worship Practices in Islamic Senior High Schools - Sayuti, Lalu; Burhanudin, Nunu; Salmiwati; Yaqin, Lalu Nurul; Famuji, Untung (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study developed and evaluated a “Patju”-based religious culture model to improve students’ worship practices in Nahdlatul Wathan Islamic senior high schools in East Lombok, West Nusa Tenggara, Indonesia. The study was motivated by the need to transform school religious routines from formal compliance into internalised worship discipline grounded in local wisdom and Islamic character values. A research and development design using the ADDIE framework was employed, consisting of analysis, design, development, implementation, and evaluation stages. The study involved three Islamic senior high schools, with data collected through observation, interviews, documentation, questionnaires, expert validation, individual trials, and group trials. Qualitative data were analysed through data reduction, data display, and conclusion drawing, while quantitative data were analysed using descriptive statistics to determine the model’s validity, practicality, and effectiveness. The findings showed that the developed model and its supporting prayer module were valid, with an overall validation score of 4.46. The effectiveness test indicated an increase in students’ worship practice scores from approximately 2.41 before implementation to 4.21–4.22 after implementation. The practicality test also showed positive results, with post-implementation practicality scores ranging from 4.13 to 4.22. These findings indicate that the model improved students’ prayer discipline, religious responsibility, honesty in worship reporting, peer support, and motivation to enhance the quality of worship. This study contributes to Islamic education scholarship by offering a culturally responsive religious culture model that integrates Lombok’s local value of “Patju” with structured worship habituation and character formation in Islamic senior high schools.